A disseminação da informação: o bibliotecário como mediador da informação especializada - SILVA, Raquel Carvalho da (2018)
Information is fundamental to acquire knowledge, this provides new paths towards what is sought in professional life, because only through much reading can be how to argue and describe new studies. In this respect the research brings the relevant profession of the librarian, the professional who had to reinvent himself all the time, changing his way of interacting with the work environment and with individuals, with the way to work before was just to treat the information to keep in the collections, today must treat and think about how you will do to disseminate to your audience or potential audience. Through bibliographic research, in documents selected in databases, scientific journals and academic sites in the areas of Library and Information Science, contents of the most relevant articles for the development of this research, for librarianship mediation and dissemination of information, for nutrition content such as integral use of food and the right to food. Therefore, through this multidisciplinary study it was possible to identify how this information professional can contribute with their skills, skills and social work.